2020
DOI: 10.1111/anae.15203
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of postoperative respiratory complications associated with the use of desflurane and sevoflurane: a single‐centre cohort study

Abstract: Sevoflurane and desflurane are the most commonly used volatile anaesthetics for maintenance of anaesthesia. In this study, we aimed to evaluate the relationship between choice of volatile anaesthetic and early postoperative respiratory complications, and to address a critical knowledge gap in safety outcomes between these two commonly used agents. We performed a retrospective analysis of adult (non-cardiac surgery) patients who received sevoflurane or desflurane for the maintenance of general anaesthesia at ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…A recent observational study of over 100,000 cases by Zucco and colleagues, for example, found no difference in postoperative pulmonary complications between patients anaesthetised with sevoflurane and desflurane when adjusted for confounding factors. 8 One potential advantage of desflurane is the faster time to recovery of consciousness and tracheal extubation. However, whilst meta-analyses of randomised controlled trials (RCTs) have confirmed that this is consistently a statistically significant finding (table 1), the magnitude of this effect is minimal (only a few minutes in most circumstances), and it does not appear that this translates to shorter patient stays in the post-anaesthesia care unit (PACU).…”
Section: Desflurane In Modern Anaesthetic Practice: Walking On Thin Ice(caps)?mentioning
confidence: 99%
See 4 more Smart Citations
“…A recent observational study of over 100,000 cases by Zucco and colleagues, for example, found no difference in postoperative pulmonary complications between patients anaesthetised with sevoflurane and desflurane when adjusted for confounding factors. 8 One potential advantage of desflurane is the faster time to recovery of consciousness and tracheal extubation. However, whilst meta-analyses of randomised controlled trials (RCTs) have confirmed that this is consistently a statistically significant finding (table 1), the magnitude of this effect is minimal (only a few minutes in most circumstances), and it does not appear that this translates to shorter patient stays in the post-anaesthesia care unit (PACU).…”
Section: Desflurane In Modern Anaesthetic Practice: Walking On Thin Ice(caps)?mentioning
confidence: 99%
“…However, whilst meta-analyses of randomised controlled trials (RCTs) have confirmed that this is consistently a statistically significant finding (table 1), the magnitude of this effect is minimal (only a few minutes in most circumstances), and it does not appear that this translates to shorter patient stays in the post-anaesthesia care unit (PACU). [8][9][10][11][12]14 Furthermore, as pointed out by Macario and colleagues, because RCT study protocols tend to require the use of a constant concentration of general anaesthetic agent up to the point of wound closure, the common clinical practice of tapering the anaesthetic dose as the surgical stimulus reduces is not represented, and this may further reduce any 'real world' difference between agents. 10 We contend that a trivially more rapid emergence from general anaesthesia with desflurane compared to sevoflurane may be of greater promotional benefit to the manufacturer than either clinical benefit to the patient or organisational benefit to surgical operating efficiency.…”
Section: Desflurane In Modern Anaesthetic Practice: Walking On Thin Ice(caps)?mentioning
confidence: 99%
See 3 more Smart Citations